CAN TOXIC MASCULINITIES BE DE-RADICALISED?: MAPPING THE DYNAMICS AND SPREAD OF INCEL IDEOLOGY ONLINE - Ging, Debbie; Brace, Lewys; Baele, Stephane (AoIR Selected Papers of Internet Research, 2023)
In recent years, male supremacist and anti-women formations have become increasingly prevalent online. In particular, considerable attention has been focused on the incel (involuntary celibate) community due to a number of high-profile mass killings in the United States, Canada and, more recently, the UK. Incel ideology is a misogynistic formation, whose male proponents blame women for their lack of sexual activity. It operates in the broader virtual space of the manosphere, a loose conglomerate of online communities spread across various digital platforms, which are united in their antipathy toward feminism, their belief in evolutionary psychology and their adherence to the Red Pill (a process of enlightenment, whereby one comes to understand the world as a liberal feminist conspiracy that disadvantages men). This research tracks the dynamic pathways by which incel ideology spreads within and across online communities, digital platforms and geographical spaces, with a view to better understanding processes of radicalization, including ‘algorithmic radicalization.’ We also explore the dynamic interplay between incel and alt-right rhetoric. Understanding the contagion dynamics of extremist ideas - how such ideas circulate, gain new audiences, and morph into new ones - is crucial to researchers, educators, platforms and security practitioners: However, theoretical and practical understanding of the online contagion of extremist ideologies is lacking. It is only by understanding these ‘pilling pipelines’ (Ging and Murphy 2021) that effective interventions can be developed, whether educational, technological, legal or platform-governance-related.